2008
DOI: 10.1021/np8003497
|View full text |Cite
|
Sign up to set email alerts
|

Mycophenolic Derivatives from Eupenicillium parvum

Abstract: A new compound, euparvic acid (1, C14H16O6), and the known compounds 5,7-dihydroxy-4-methylphthalide (2), 6-(3-carboxybutyl)-7-hydroxy-5-methoxy-4-methylphthalan-1-one (3), 6-(5-carboxy-3-methylpent-2-enyl)-7-hydroxy-5-methoxy-4-methylphthalan-1-one (4), and 6-(5-carboxy-4-hydroxy-3-methylpent-2-enyl)-7-hydroxy-5-methoxy-4-methylphthalan-1-one (5) were isolated from the EtOAc extract of Eupenicillium parvum. The structure of 1 was determined by interpretation of MS and homo- and heteronuclear 2D NMR spectrosco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 11 publications
0
19
0
2
Order By: Relevance
“…The 1 H-, 13 C-and 2D-NMR data of 2 suggested the presence of a phthalan-1-one system with a long aliphatic chain, and indicated that 2 should be a mycophenolic derivative. 10 This partial structure of phthalan-1-one was established by spectral data in comparison with those of MPA (1) and supported by its heteronuclear multiple bond coherence (HMBC) correlations from H-3 to C-1, 4, 7a, 3a, CH 3 -8 to C-4, C-5, C-3a and CH 3 -9 to C-5. This result was further supported by the UV absorption at 250 and 304 nm, which was very similar to that of MPA (1).…”
mentioning
confidence: 76%
“…The 1 H-, 13 C-and 2D-NMR data of 2 suggested the presence of a phthalan-1-one system with a long aliphatic chain, and indicated that 2 should be a mycophenolic derivative. 10 This partial structure of phthalan-1-one was established by spectral data in comparison with those of MPA (1) and supported by its heteronuclear multiple bond coherence (HMBC) correlations from H-3 to C-1, 4, 7a, 3a, CH 3 -8 to C-4, C-5, C-3a and CH 3 -9 to C-5. This result was further supported by the UV absorption at 250 and 304 nm, which was very similar to that of MPA (1).…”
mentioning
confidence: 76%
“…The following known compounds were also identified; flavoglaucin ( 3 ), 9 tetrahydroauroglaucin ( 4 ), 10 dihydroauroglaucin ( 5 ), 11 auroglaucin ( 6 ), 11 and 2-(2′,3-epoxy-1′,3′-heptadienyl)- 6-hydroxy-5-(3-methyl-2-butenyl)benzaldehyde ( 7 ), 9 echinulin ( 8 ), 12 and 5,7-dihydroxy-4-methylphthalide ( 9 ), 13 and this was confirmed by comparison of physical and spectroscopic data (UV, 1 H and 13 C NMR, and MS) with corresponding authentic samples or literature values.…”
mentioning
confidence: 99%
“…However, natural phthalides such as (5,7-dihydroxy-4-methylphthalide) and (5,7-dimethoxyisobenzofuran-1(3H)-one) have already been reported (Puel et al 2005, Fujimoto et al 1999, Habib et al 2008, Sun et al 2009). That ANGELA M.M.P.…”
Section: In the Ms/ms Experiments (Esi -Negativementioning
confidence: 99%